Pengaruh BTD, IOS, Dan Struktur Modal Terhadap Kualitas Laba Pada Sektor Consumer Non-Cyclicals - Giawan Nur Fitria; Mita Amelia (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2026)
This quantitative research examines the influence of BTD, IOS, and Capital Structure on Earnings Quality. It uses secondary data from the annual reports of consumer no- cyclicals companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The purposive sampling method was used to obtain a sample of 170 samples, by analyzing a multiple linear regression model. This research study revealed that BTD and Capital Structure did not have a significant effect on Earnings Quality. Meanwhile, IOS had a significant negative effect on Earnings Quality.